ADOLESCENTS' SOCIAL IDENTIFICATION CRISIS AS A FACTOR OF THE ORIGIN OF THE PROPENSITY TO COMMIT CRIME - Umidullayeva Marjona (Innovate Conferences, 2025)
This article analyzes the social identity crisis of adolescents as a factor of the origin of the tendency to commit crime. The influence of the identity crisis, family environment, school and peer group is considered as the main determinants that increase the risk of crime.
Keywords: Adolescence, social adaptation, crime, identification, crisis, psychological analysis, prevention.